Incidence of Research Gap Years in Orthopaedic Residency Applicants: The New Standard?. (November 2021) - Cotter, Eric J.; Polce, Evan M.; Lee, Eric; Williams, Kathryn L.; Spiker, Andrea M.; Grogan, Brian F.; Lang, Gerald J.
Abstract : Introduction: The purpose of this study was to (1) determine the incidence of a research gap year (RGY) in orthopaedic residency applicants at a single institution over a seven-year span; (2) compare applicant characteristics between applicants who did a RGY with those who did not, and (3) report variables associated with match success for RGY applicants. Methods: Applicants who reported taking a year out from medical school to pursue research on their Electronic Residency Application Service to a single institution from 2014 to 2015 through 2020 to 2021 were reviewed. Results: A strong positive correlation was noted between the percentage of applicants who participated in a RGY and time (Pearson correlation: r = 0.945 [95% confidence interval (CI), 0.6660.992], P = 0.001). Over the study period, 11% of applicants had done a RGY, most commonly after their third year of medical school (82.7%). Most RGY applicants matched orthopaedics (72.8%) and 19.4% matched at the same institution they did their RGY. Conclusion: The percentage of RGY applicants to the study institution nearly doubled between 2014 to 2015 and 2020 to 2021. RGY applicants had a higher match rate than nationally published match rates. Further study is needed on a national level.